PENGARUH KEBUTUHAN MENCARI VARIASI, PERSEPSI HARGA DAN CELEBRITY ENDORSER TERHADAP BRAND SWITCHING (Studi Empiris Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang) (Students' Journal of Economic and Management, 2014)
This study is done to analyze the effect of variables variety seeking, price perception, and celebrity endorser against brand switching behavior GSM card in among students. Respondents of this study were students who ever switch brands totaling 100 respondents. The sampling technique using sampling Purposive, then analysed using multiple linear regression. The results of this study indicate that brand switching behavior (Switching Behavior), significantly and positively influenced by the variety seeking and price perception. celebrity endorser variable is not significant and positive influence on brand switching. The most dominant variable affecting brand switching behavior a GSM card is price perception.whereas variable small influence is a variable celebrity endorser.For future researchers, the data collection can be performed to consumers on various pulse counters in order to provide more complete information. Keyword:Variety seeking, Priceperception, Celebrity endorser and Brand switching